Global and national visibility of management research methodology scholars – the case of Poland - Kosch, Oskar; Szarucki, Marek; Skačkauskienė, Ilona (Business: Theory and Practice, 2023)
Developing research methodology contributes to better management research outputs, links better management theory to business practice, as well as enriches the academic training received by the students at universities. Researchers might be tempted to provide generalizations on management research methodology based on global bibliographic databases, such as Scopus and Web of Science, and draw conclusions on the possible educational outline. However, since students are educated mainly in national languages, the literature in these languages might gain priority over more internationally recognized publications available only in English. Then, the question arises if scholars who might be recognized globally due to their presence in large, international bibliographic databases retain their visibility and influence at the national level. We conduct a comparative bibliometric study using Scopus, Web of Science, and BazEkon to answer this question. Our research reveals that for the case of Poland, information and social networks of management methodology scholars do not support the assumption of direct visibility of such global scholars at the national level, thus putting into question the reliability of global bibliographic databases to study management at the national level.